2020
DOI: 10.3389/fsurg.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo Performance of Seven Commercially Available Demineralized Bone Matrix Fiber and Putty Products in a Rat Posterolateral Fusion Model

Abstract: Introduction: Demineralized bone matrix (DBM) is a widely used bone graft in spinal fusion. Most commercial DBMs are composed of demineralized bone particles (∼125-800 microns) suspended in a carrier that provides improved handling but dilutes the osteoinductive component. DBM fibers (DBF) provide improved osteoconductivity and do not require a carrier. It has been suggested that 100% DBF may offer improved performance over particulate-based DBMs with carrier.Study Design: Seven commercially available DBM prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In this study, microtomographic images gave detailed information on the progression of bone repair over time in both groups, as reported in other studies 28 . The rate of tissue repair increased at the experimental times (15,30,60 and 90 days). The macroscopically structure and regeneration was similar in both groups, but the healing rate was faster in control group.…”
Section: ■ Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In this study, microtomographic images gave detailed information on the progression of bone repair over time in both groups, as reported in other studies 28 . The rate of tissue repair increased at the experimental times (15,30,60 and 90 days). The macroscopically structure and regeneration was similar in both groups, but the healing rate was faster in control group.…”
Section: ■ Discussionmentioning
confidence: 89%
“…Statistical analysis was performed by applying parametric tests. To compare the results obtained in the control group (CG), the matrix group (MG) and the different euthanasia times (15,30, 60 and 90 days), the ANOVA analysis of variance test was used. The means between control group and matrix at each euthanasia time were then compared using the T student test, considering a significance level of 95% (p <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The varying BMP concentration in commercial DBM greatly impacts its clinical efficacy [ 37 ]. In an athymic rat model, a large variation in fusion performance of DBM and demineralized bone fiber (DBF) of seven commercial products (StrandTM Family, Propel ® DBM Fibers, Vesuvius ® Demineralized Fibers, Optium ® DBM Putty, Grafton ® DBF, Grafton Flex, and DBX ® Putty) was observed, and outcomes indicated a detrimental influence of the carrier on the fusion performance; hence, DBM allografts should be carefully selected [ 112 ]. Research has also shown that different commercial DBM products (Grafton Putty, DBX Putty, and AlloMatrix Injectable Putty) may results in varying magnitude of new bone formation and radiographically evident spinal fusion [ 113 ].…”
Section: Currently Employed Surgical Materials For Bone Grafting Amentioning
confidence: 99%